The effect of innovative mindset and behavior on innovation performance and competitive advantage: a case of halal SMEs owner-managers from Malaysian energy-intensive industry - Jaaffar A.H.; Abd Majid N.; Kasavan S.; Isa A.; Alwi M.N.R.; Zahari A.R. (Springer Science and Business Media Deutschland GmbH, 2025)
Malaysia was ranked 32nd on the Global Competitiveness Index in 2022, which denotes that the level of R&D and productivity in SMEs in Malaysia needs to be improved.Therefore, more research is needed to ensure it remains competitive in the global halal marketplace by using innovative concepts as a culture to promote energy-intensive halal SMEs. This study examines the sequential influence of an innovative mindset, behavior, and performance on competitive advantage among SME owner-managers embarking on halal businesses. Data were gathered from SME owner-managers from the halal energy-intensive industry by conducting a self-administered and online-based survey involving 140 respondents. Data were analyzed with the partial least squares technique (SmartPLS 3.0). The results of this study show that innovative behavior was a direct result of an innovative mindset. On the other hand, innovative behavior produced innovation performance, which in turn produced a competitive advantage. This study shows that SMEs owner-managers of halal energy-intensive industries need possess both innovative behavior and innovative attitude as valuable assets. Moreover, a key component in their ability to gain a competitive advantage is their performance in innovation. ? 2023, The Author(s).